Susanne Wilson on a horse - Unknown:::Creator::::::::::::
Photograph shows Susanne B. Wilson sitting sidesaddle on a horse with a flower lei around its neck. Susie is wearing a cowboy hat and is smiling and waving. Another women is standing at the horse's head and holding the reins. They are indoors and may be on a stage. The photograph was taken at the San Jose Convention Center in November 1990.